Kerusakan ekosistem alam akibat keserakahan tangan manusia - rohmah, ziyada (Maliki Interdisciplinary Journal, 2026)
Environmental ecosystem degradation is one of the most severe consequences of human behavior driven by economic interests and unlimited exploitation. Activities such as deforestation, excessive mining, industrial pollution, and massive land conversion have disrupted the ecological balance that sustains life. This phenomenon not only leads to biodiversity loss but also triggers climate change, soil degradation, and a decline in water and air quality. This article aims to examine the relationship between human greed and the rate of ecosystem destruction through a descriptive-analytical approach. Data are reviewed from scientific literature, environmental reports, and recent case studies from various regions. The analysis reveals that environmental ethics awareness remains low, while conservation policies are often weakened by short-term economic interests. Mitigation efforts require a paradigm shift in human interaction with nature from exploitation toward sustainability. Therefore, synergy among governments, communities, and industries is essential to restore ecological balance and ensure the sustainability of life in the future.